2018
DOI: 10.1371/journal.pone.0202393
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive scoring systems predict hepatic and extra-hepatic cancers in patients with nonalcoholic fatty liver disease

Abstract: BackgroundLiver fibrosis predicts liver-related morbidity and mortality in patients with non-alcoholic fatty liver disease (NAFLD). Non-invasive scores correlate with the degree of liver fibrosis in these patients.Aims and methodsTo investigate the accuracy of noninvasive scoring systems in predicting long-term outcomes and cancer incidence of patients with NAFLD, we performed a single-center retrospective study of patients with biopsy proven NAFLD. Mean follow up period was 100 months. Outcomes included liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 29 publications
1
42
1
1
Order By: Relevance
“…Kim and colleaguesa previously carried out a population‐based study which evaluated subjects with evidence of NAFLD in NHANES and demonstrated that APRI (and NFS) were associated with all‐cause mortality in patients with NAFLD identified by ultrasonography. FIB‐4 and APRI scores have also been shown to be associated with mortality in previous cohort studies of individuals with biopsy‐proven NAFLD . However, a 2018 systematic review and meta‐analysis of eight studies (four of which provided data for FIB‐4 and APRI) investigated the association between non‐invasive scores and mortality, and this analysis included the quoted studies by Kim et al and Angulo et al In contrast to our results obtained in a much larger single cohort, this meta‐analysis of four studies with data for FIB‐4 and APRI scores failed to show that either FIB‐4 or APRI scores were associated with all‐cause mortality …”
Section: Discussioncontrasting
confidence: 56%
“…Kim and colleaguesa previously carried out a population‐based study which evaluated subjects with evidence of NAFLD in NHANES and demonstrated that APRI (and NFS) were associated with all‐cause mortality in patients with NAFLD identified by ultrasonography. FIB‐4 and APRI scores have also been shown to be associated with mortality in previous cohort studies of individuals with biopsy‐proven NAFLD . However, a 2018 systematic review and meta‐analysis of eight studies (four of which provided data for FIB‐4 and APRI) investigated the association between non‐invasive scores and mortality, and this analysis included the quoted studies by Kim et al and Angulo et al In contrast to our results obtained in a much larger single cohort, this meta‐analysis of four studies with data for FIB‐4 and APRI scores failed to show that either FIB‐4 or APRI scores were associated with all‐cause mortality …”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, a significant proportion of patients fall within an indeterminate zone, consequently such scores are primarily used in the clinic to exclude a diagnosis of advanced liver fibrosis . Whilst having limited diagnostic value, scores such as FIB‐4 and NAFLD fibrosis score have shown some prognostic value …”
Section: Non‐invasive Assessment Of Liver Fibrosismentioning
confidence: 99%
“…Furthermore, a significant proportion of patients fall within an indeterminate zone, consequently such scores are primarily used in the clinic to exclude a diagnosis of advanced liver fibrosis 71,72. Whilst having limited diagnostic value, scores such as FIB-4 and NAFLD fibrosis score have shown some prognostic value 73,74. 11 | D IREC T B I OMARK ER S OF HEPATIC FIB ROS ISCollagens, as discussed earlier, are the principal component of the fibrotic scars that develop as a result of CLD.…”
mentioning
confidence: 99%
“…The increasing burden of chronic liver disease, including hepatitis with HBV or HBC, or caused by NAFLD, and the need for risk stratification to better personalized treatment and monitoring for HCC, has led to the evolution of such clinical measures as non‐invasive markers or models for liver fibrosis. Scoring models that use commonly measured serum markers of hepatic impairment include FIB‐4 and APRI, which were originally developed for patients with chronic hepatitis C viral infection and have subsequently been used for other hepatic disorders, including NAFLD . The ALBI grade was proposed as a simple and objective method for assessment of liver function in HCC as a result of an international collaborative study .…”
Section: Discussionmentioning
confidence: 99%
“…Scoring models that use commonly measured serum markers of hepatic impairment include FIB-4 and APRI, which were originally developed for patients with chronic hepatitis C viral infection and have subsequently been used for other hepatic disorders, including NAFLD. 22 The ALBI grade was proposed as a simple and objective method for assessment of liver function in HCC as a result of an international collaborative study. 23 Although ALBI grade has been validated externally in several other studies, 7,8,24,25 it does not incorporate portal hypertension or liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%